Disparity Between Indications for and Utilization of Implantable Cardioverter Defibrillators in Asian Patients With Heart Failure. Issue 11 (November 2017) - Chia, Yvonne May Fen; Teng, Tiew-Hwa Katherine; Tan, Eugene S.J.; Tay, Wan Ting; Richards, A. Mark; Chin, Calvin Woon Loong; Shimizu, Wataru; Park, Sang Weon; Hung, Chung-Lieh; Ling, Lieng H.; Ngarmukos, Tachapong; Omar, Razali; et al.
Abstract : Background—: Implantable cardioverter defibrillators (ICDs) are lifesaving devices for patients with heart failure (HF) and reduced ejection fraction. However, utilization and determinants of ICD insertion in Asia are poorly defined. We determined the utilization, associations of ICD uptake, patient-perceived barriers to device therapy and, impact of ICDs on mortality in Asian patients with HF. Methods and Results—: Using the prospective ASIAN-HF (Asian Sudden Cardiac Death in Heart Failure) registry, 5276 patients with symptomatic HF and reduced ejection fraction (HFrEF) from 11 Asian regions and across 3 income regions (high: Hong Kong, Japan, Korea, Singapore, and Taiwan; middle: China, Malaysia, and Thailand; and low: India, Indonesia, and Philippines) were studied. ICD utilization, clinical characteristics, as well as device perception and knowledge, were assessed at baseline among ICD-eligible patients (EF ⩽35% and New York Heart Association Class II-III). Patients were followed for the primary outcome of all-cause mortality. Among 3240 ICD-eligible patients (mean age 58.9±12.9 years, 79.1% men), 389 (12%) were ICD recipients. Utilization varied across Asia (from 1.5% in Indonesia to 52.5% in Japan) with a trend toward greater uptake in regions with government reimbursement for ICDs and lower out-of-pocket healthcare expenditure. ICD (versus non-ICD) recipients were more likely to be older (63±11 versus 58±13 year; P <0.001), have tertiary (versus ⩽primary) education (34.9% versus 18.1%; P <0.001) and be residing in a high (versus low) income region (64.5% versus 36.5%; P <0.001). Among 2000 ICD nonrecipients surveyed, 55% were either unaware of the benefits of, or needed more information on, device therapy. ICD implantation reduced risks of all-cause mortality (hazard ratio, 0.71; 95% confidence interval, 0.52–0.97) and sudden cardiac deaths (hazard ratio, 0.33; 95% confidence interval, 0.14–0.79) over a median follow-up of 417 days. Conclusions—: ICDs reduce mortality risk, yet utilization in Asia is low; with disparity across geographic regions and socioeconomic status. Better patient education and targeted healthcare reforms in extending ICD reimbursement may improve access. Clinical Trial Registration—: URL:https://clinicaltrials.gov/ct2/show/NCT01633398 . Unique identifier: NCT01633398.